Radiation assisted synthesis of nanosized barium zirconate - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Pasricha, R.; Bapat, Malini S. (Radiation Physics and Chemistry, 2006)
This paper reports the synthesis of refractory barium zirconate using solid-state reactive precursors subjected to gamma-radiations of a Co-60 source. Influence of varying doses on the formation of cubic phase of BaZrO3 has been investigated with the stepwise analysis of the intermediate products by means of FT-IR, XRD and TGA techniques. TEM depicts the nanospherical nature of the BaZrO3 particles. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; gamma-radiation; Nanoparticles; perovskite; refractory; XRD